Characterization of Clove Oil Nanoparticles and Their Insecticidal Activity against Cryptolestes ferrugineus (Stephens) (Coleoptera: Laemophloeidae) - Silvi Ikawati; Toto Himawan; Abdul Latief Abadi; Hagus Tarno (AGRIVITA, Journal of Agricultural Science, 2021)
The application of essential oils to storage pest control requires an appropriate formulation formed by biodegradable compounds. This formulation should protect essential oils from degradation and evaporation while simultaneously allowing sustained release. This study aims to characterize nanoparticles loaded by clove essential oil-based polymer polyethylene glycol (PEG) and to investigate their insecticidal activity. In this study, clove oil solid dispersion was prepared using the fusion or melting-dispersion method with polyethylene glycol 6000 (PEG 6000) to form a binary solid dispersion system. The ratio of 10% of clove oil to PEG was optimal and had low PDI, small size, and the highest clove oil loading efficiency. Their size changed from 179 to 197 nm after 24 weeks of storage and the loading efficiency decreased for about 36%. Clove oil formulation in nanoparticles could not enhance the toxicity of clove oil but yet still showed high contact toxicity to C. ferrugineus. These formulations also have the slow and persistent release of the bioactive.